The Effect of Liquidity Risk Management, Leverage Policy, and Cost Control on Financial Growth in Construction Companies in East Java - Judijanto, Loso; Basiri , Syamsu; Yuliawati, Refiana (West Science Interdisciplinary Studies, 2024)
This study examines the effects of Cost Control, Leverage Policy, and Liquidity Risk Management on Financial Growth in construction companies in East Java. Utilizing a quantitative approach, data was collected from 180 respondents using a Likert scale (1-5), and analyzed through Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The results indicate that Cost Control has the most significant impact on Financial Growth, followed by Leverage Policy, and Liquidity Risk Management. The study highlights the importance of efficient cost management and prudent leverage practices in promoting financial stability and growth in the construction sector. The findings underscore the need for construction companies to implement strategic financial management practices to enhance their competitive advantage and long-term sustainability.